2022
DOI: 10.3390/jcdd9010016
|View full text |Cite
|
Sign up to set email alerts
|

News from the Cold Chamber: Clinical Experiences of POLARx versus Arctic Front Advance for Single-Shot Pulmonary Vein Isolation

Abstract: Cryoballoon (CB)-guided pulmonary vein isolation (PVI) represents a cornerstone in the treatment of atrial fibrillation (AF). Recently, a novel balloon-guided single shot device (POLARx, Boston Scientific) was designed. Our study aimed to compare the efficacy, safety and characteristics of the novel CB system with the established one (Arctic Front Advance (Pro), AFA, Medtronic). A total number of 596 patients undergoing CB-guided ablation for AF were included. 65 patients (65.0 ± 11.6, 31% female) undergoing P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 24 publications
4
20
1
Order By: Relevance
“…Enlarged PVs and the related CSOA might impede complete electrical isolation of the PVs and inadequate isolation or lesion formation increases the risk for PV reconnection. In a prior study, we documented that the presence of an enlarged PV (LCV) is associated with more freeze cycles for complete PVI [ 22 ]. Larger PVs seem to require more freeze applications for complete PVI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enlarged PVs and the related CSOA might impede complete electrical isolation of the PVs and inadequate isolation or lesion formation increases the risk for PV reconnection. In a prior study, we documented that the presence of an enlarged PV (LCV) is associated with more freeze cycles for complete PVI [ 22 ]. Larger PVs seem to require more freeze applications for complete PVI.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond that, the handling of the POLARx system is comparably smart and straightforward due to improved material properties. The POLARSTEATH appears to be softer and more flexible [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the outcomes first freeze isolation RSPV, first freeze isolation RIPV, TTI recording RSPV and TTI RIPV, the between-study heterogeneity became < 50 % after the exclusion of a single study, however, the overall effect size did not change. Heterogeneity for the outcome of first freeze isolation LIPV was driven primarily by the study of Guckel et al [13] After the exclusion of this study, no difference between was detected in the likelihood of first freeze isolation LIPV (P = 0.16) (Supplemental figure S5 A). Heterogeneity for the outcomes of TTI recording LSPV, TTI LSPV and TTI RSPV was driven primarily by the study of Moser et al [16] After the exclusion of this study, TTI recording LSPV and TTI LSPV became in favour of POLARx (P = 0.004 and P = 0.02, respectively) (Supplemental figure S5 B and S5C).…”
Section: Resultsmentioning
confidence: 97%
“…1 ). [8] , [9] , [10] , [11] , [13] , [14] , [15] , [16] All included studies were observational in design and found to be of good quality based on the Newcastle Ottawa scale (Supplemental table S1 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation